The National Solid Waste Policy and the Sustainable Development Goals: Challenges and Opportunities for the Construction Sector in Brazil - Peres , Evair Fonseca; Guerra , José Baltazar Salgueirinho Osório de Andrade; Nascimento, Ana Paula Branco do (Technical and Scientific Journal Green Cities, 2025)
Objective: Analyze the implementation of the National Solid Waste Policy (PNRS) in the Brazilian construction sector, assessing its alignment with the Sustainable Development Goals (SDGs), with a focus on SDG 12: “Responsible Consumption and Production”.Methodology: The research adopted a qualitative approach based on bibliographic and documentary review. Eligibility criteria were used to select studies from 2010 to 2025, including official reports, scientific articles, and national legislation.Originality/Relevance: The study fills a theoretical gap by integrating the analysis of the PNRS with specific SDG targets, especially SDG 12. It confronts theoretical legislative advances with the practical implementation challenges in municipalities.Results: The PNRS still faces significant barriers such as the persistence of open dumps in 29.6% of municipalities and low effectiveness in selective collection. Civil construction consumes 40% of natural resources and generates 25–30% of urban solid waste.Theoretical/Methodological Contributions: The study provides an integrated analysis linking environmental policy, national data, and UN goals, suggesting reinforcement strategies for PNRS through partnerships, sustainable planning, and green technology.Social and Environmental Contributions: It highlights the role of social inclusion through waste picker cooperatives and circular economy practices, showing their impact on employment, regional equality, and contribution to the 2030 Agenda.
Keywords: Solid waste; civil construction; National Solid Waste Policy (PNRS),; SDGs; sustainability